Green Sustainability: Towards Innovative Digital Transformation Proceedings of ITAF 2023 - Magdi, Dalia; El-Fetouh, Ahmed Abou; Mamdouh, Mohamed; Joshi, Amit (Lecture Notes in Networks and Systems, 2023)
XVI, 390 p. 106 illus., 86 illus. in color.